Implementasi Sistem Evaluasi Formatif Berbasis Game "Kahoot dan Quizizz" untuk Meningkatkan Motivasi Belajar Mahasiswa di Masa Pandemi (Studi pada Mata Kuliah Ekonomi Islam) - Cut Muftia Keumala; Zamzami Zainuddin; Fauzan Fauzan (Jurnal Inovasi Pendidikan Ekonomi (JIPE), 2021)
This study aims to implement an innovative and fun learning strategy, namely a formative evaluation based on the game "Kahoot and Quizizz" to increase student learning motivation during the Covid-19 pandemic period. The study was conducted for Islamic Economics courses at Sekolah Tinggi Ilmu Ekonomi Lhokseumawe. Mixed-method research was employed in collecting data on students during the teaching-learning process for one semester. Quantitative data were obtained and analyzed from students' tests or formative evaluations and through questionnaires. Meanwhile, the qualitative data were obtained from personal in-depth interviews with several students from the experimental class. The results of this study indicate that the employment of the Kahoot and Quizizz game platforms has a positive impact on student achievement and motivation. This can be recognized from the results of the formative assessment data analysis and the responses from the questionnaire. The qualitative data also confers a positive value from the use of the Kahoot and Quizizz game applications. Four positive values emerged from the results of interviews with students regarding the application of these two applications, namely: fun, nothing boring, innovative assessment methods, and active classes.